Zrównoważony rozwój jako podstawa polskiej polityki ekologicznej - w poszukiwaniu nowej formuły kompromisu ekologii z ekonomią - Maciej Rudnicki (Studia Ecologiae et Bioethicae)
The article includes detailed analysises of basic terms and concepts, especially the phrases: balanced development, ecological politics, compromise, ecology, economy, these analysises show the rich context of international science researches, European Union, Poland and they present wide historical and contemporary aspect.